Ultra-high performance concrete based on combined curing method and preparation method thereof
By using combined curing methods and specific proportions of raw materials in the preparation of ultra-high performance concrete, the problems of harsh materials and high costs are solved, and the effects of strength improvement, solid waste resource utilization and cost reduction are achieved.
Patent Information
- Application Number
- CN202411833712.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-04
AI Technical Summary
The material requirements of ultra-high performance concrete are relatively demanding, and production and use require more costs. The early strength develops rapidly but the later strength is extremely high, making it difficult to meet the needs of some engineering construction.
The preparation method based on combined curing methods is adopted, using P.O 42.5 cement, natural sand, silica fume, fly ash, water, water reducer and steel fibers. Through specific stirring and curing processes, the strength of concrete and the interest rate of solid waste resources are improved and the cost is reduced.
It significantly improves the strength and solid waste resource interest rate of ultra-high performance concrete, reduces production and use costs, is suitable for engineering construction with high strength requirements in the early stage, and replaces high-cost commercially available ultra-high performance concrete.
Smart Images

Figure BDA0005186166310000071
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of building materials, and in particular to an ultra-high performance concrete based on a combined curing method and a preparation method thereof. Background Art
[0002] Ultra-high performance concrete is a special engineering material with high strength, high toughness and high durability. It has good application prospects in national defense engineering, marine engineering, nuclear industry, special security and protection engineering, and municipal engineering.
[0003] Ultra-high performance concrete develops its early strength quickly and has extremely high strength in the later stages. It can replace steel and expensive organic polymers in maintenance and reinforcement projects, maintaining the integrity of the concrete system while reducing costs.
[0004] However, ultra-high performance concrete has more stringent material requirements and requires more costs to produce and use.
[0005] Therefore, a new solution to the above problems needs to be proposed. Summary of the invention
[0006] The purpose of the present invention is to provide an ultra-high performance concrete based on a combined curing method and a preparation method thereof, aiming to prepare ultra-high performance concrete by different methods, and further improve the strength of ultra-high performance concrete, increase the solid waste resource rate, and reduce costs.
[0007] To achieve the above-mentioned object, the present invention provides the following technical solution: an ultra-high performance concrete based on a combined curing method, comprising PO 42.5 cement, natural sand, silica fume, fly ash, water, a water reducer and steel fiber, wherein the mass fractions of the PO 42.5 cement, natural sand, silica fume, fly ash, water, a water reducer and steel fiber are 1, 1.59, 0.25, 0.1, 0.243, 0.034 and 0.238 respectively.
[0008] PO 42.5 cement plays the role of bonding various materials, making them all connected as one, thereby improving the strength, stability and durability of concrete; silica fume has a small particle size, which can act as a micro-filler, making the concrete more compact, and can improve the concrete's impermeability and resistance to saline-alkali water erosion. Fly ash has volcanic ash properties, which can inhibit hydration heat. Volcanic ash reactions can produce insoluble calcium silicate hydrates, which improve the concrete's impermeability. The main role of steel fiber in concrete is to enhance the overall performance and structural safety of concrete by improving tensile strength, impact resistance, crack resistance, toughness and deformation capacity, as well as durability and fatigue resistance; it can also connect concrete into a whole, which is beneficial to preventing concrete cracking and damage. Water reducer can improve fluidity when the mix ratio remains unchanged; reduce water consumption, reduce water-cement ratio and improve strength when the fluidity and cement dosage remain unchanged; save cement consumption and reduce costs when the fluidity and strength remain unchanged. Natural sand particles are uniform in shape and can fill the internal pores of concrete to improve density and overall strength.
[0009] Furthermore, the particle gradation range of the PO 42.5 cement is relatively narrow, with 3-32 μm particles accounting for about 60-70%; the silica fume SiO2 content is about 85-90%; and the fly ash is Class II non-high-quality fly ash.
[0010] Furthermore, the natural sand is divided into three groups according to the particle size range: 0.15-0.3 mm, 0.3-0.6 mm and 0.6-1.18 mm, and is mixed in a mass ratio of 1:3:3 before use.
[0011] Furthermore, the natural sand, silica ash and fly ash are all taken from Ordos City. The silica ash and fly ash are solid wastes from local power plants and crystalline silicon plants. The prices of the silica ash and fly ash are about 30% lower than those of deeply processed silica ash and fly ash. The application of the two has greatly improved environmental benefits, reduced economic costs, and promoted the development of a low-carbon economy.
[0012] Furthermore, the water reducer is a polycarboxylic acid high-efficiency water reducer, which is prepared by adding polyether water reducer monomer, hydrogen peroxide, VC, acrylic acid and mercaptopropyl functional monomer and then causing redox reaction.
[0013] Furthermore, the steel fiber is a thin hook steel fiber with a specification of 0.22mm (diameter)×13mm (length), which is made from waste tires and costs about 50% of the cost of ordinary steel fibers with a diameter of 0.1mm. The hook of the steel fiber increases the friction between it and the concrete material, greatly improving the ability of the concrete to resist external loads.
[0014] A method for preparing ultra-high performance concrete based on a combined curing method, comprising at least:
[0015] Step 1: Pour cement, natural sand, silica fume and fly ash into a planetary mixer in proportion, and stir at high speed for 2 minutes until uniform. Set the speed to 50 rpm for rotation and 20 rpm for revolution.
[0016] Step 2: Mix water and water reducing agent in proportion and add them into the mixer. Stir at high speed for 8 minutes. Set the speed to 50 rpm and 20 rpm.
[0017] Step 3: Evenly scatter the steel fibers in the mixer, restart the machine and stir at high speed for 2 minutes to evenly distribute the steel fibers in the concrete. Set the speed to 50 rpm for rotation and 20 rpm for revolution.
[0018] Step 4: Continue stirring at high speed for 5 minutes, with the speed set to 50 rpm for rotation and 20 rpm for revolution;
[0019] Step 5: After the mixing is completed, pour the prepared flowable ultra-high performance concrete into the mold in three times. After each pouring, it needs to be fully vibrated for 60 seconds.
[0020] Step 6: After standing for 1 day, remove the mold;
[0021] Step 7: Place the concrete test block in a standard curing box with a temperature of 21°C and a humidity of 98% for curing for 4 days, and then transfer it to a high-temperature curing device with a temperature of 98°C and maintain it in a water bath for 3 days; the 4-day standard curing at a temperature of 21°C and a humidity of 98% allows the concrete to harden normally and avoid cracking and breakage, and the 3-day high-temperature water bath curing at a temperature of 98°C allows the early strength of the concrete to develop rapidly and avoid the occurrence of concrete shrinkage cracks.
[0022] Step 8: Conduct indoor tests to determine the compressive and flexural strengths of ultra-high performance concrete.
[0023] Furthermore, the compressive strength of the ultra-high performance concrete is 143 MPa, and the flexural strength of the ultra-high performance concrete reaches 24 MPa.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The present invention prepares ultra-high performance concrete in different ways, further improves the strength of ultra-high performance concrete, increases the solid waste resource rate, and reduces the preparation cost.
[0026] It is especially used in major engineering construction projects in Ordos City and its neighboring areas that require high early strength, reducing economic costs, improving the service performance of engineering structures, and realizing the use of local materials to prepare ultra-high performance concrete to replace the existing high-cost commercially available ultra-high performance concrete. The cementitious materials and aggregates used can be directly obtained from within the country. This not only reduces the cost of ultra-high performance concrete preparation, but also gives full play to the advantages of local resources, reduces dependence on external resources, improves the utilization rate of solid waste resources, and provides strong support for the development of related industries. DETAILED DESCRIPTION
[0027] The technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments.
[0028] Embodiment 1:
[0029] The invention discloses an ultra-high performance concrete based on a combined curing method, wherein the raw materials thereof include PO 42.5 cement, natural sand, silica fume, fly ash, water, a water reducing agent and fine hook steel fiber.
[0030] The method for preparing ultra-high performance concrete comprises:
[0031] Step 1: Use a set of sieves to screen the natural sand and divide it into three groups according to the particle size range: 0.15-0.3mm, 0.3-0.6mm, and 0.6-1.18mm. Mix them in a mass ratio of 1:3:3 to configure the selected graded natural sand.
[0032] Step 2: Pour 1 part of PO 42.5 cement, 0.25 parts of silica fume, 0.1 parts of fly ash and 1.59 parts of selected graded natural sand into a planetary mixer by mass, and dry-mix at high speed for 2 minutes until uniform. The speed is set to 50 rpm for rotation and 20 rpm for revolution.
[0033] Step 3: Mix 0.243 parts of water and 0.034 parts of high-performance water reducer by mass, add to the mixer, stir at high speed for 8 minutes, and set the speed to 50 rpm and 20 rpm.
[0034] Step 4: Evenly scatter 0.238 portions of fine hook steel fiber in the mixer, restart the machine and stir at high speed for 2 minutes to evenly distribute the steel fiber in the concrete. Set the speed to 50 rpm for rotation and 20 rpm for revolution.
[0035] Step 5: Continue stirring at high speed for 5 minutes, with the speed set to 50 rpm for rotation and 20 rpm for revolution.
[0036] Step 6: After the mixing is completed, pour the prepared flowable ultra-high performance concrete into the mold in 3 times. After each pouring, it needs to be fully vibrated, and the vibration time is about 60s.
[0037] Step 7: Let it sit for 1 day and remove the mold.
[0038] Step 8: Place the concrete test block in a standard curing box with a temperature of 21°C and a humidity of 98% for 4 days, and then transfer it to a high-temperature curing device with a temperature of 98°C and maintain it in a water bath for 3 days.
[0039] Step 9: Conduct indoor tests to determine the compressive strength and flexural strength of high performance concrete. The results are shown in Table 1.
[0040] Embodiment 2:
[0041] The invention discloses an ultra-high performance concrete based on a combined curing method, wherein the raw materials thereof include PO 42.5 cement, natural sand, silica fume, fly ash, water, a water reducing agent and fine straight steel fibers.
[0042] The method for preparing ultra-high performance concrete comprises:
[0043] Step 1: Use a set of sieves to screen the natural sand and divide it into three groups according to the particle size range: 0.15-0.3mm, 0.3-0.6mm, and 0.6-1.18mm. Mix them in a mass ratio of 1:3:3 to configure the selected graded natural sand.
[0044] Step 2: Pour 1 part of PO 42.5 cement, 0.25 parts of silica fume, 0.1 parts of fly ash and 1.59 parts of selected graded natural sand into a planetary mixer by mass, and dry-mix at high speed for 2 minutes until uniform. The speed is set to 50 rpm for rotation and 20 rpm for revolution.
[0045] Step 3: Mix 0.243 parts of water and 0.034 parts of high-performance water reducer by mass, add to the mixer, stir at high speed for 8 minutes, and set the speed to 50 rpm and 20 rpm.
[0046] Step 4: Evenly scatter 0.238 parts of fine straight steel fibers in the mixer, restart the machine and stir at high speed for 2 minutes to evenly distribute the steel fibers in the concrete. Set the speed to 50 rpm for rotation and 20 rpm for revolution.
[0047] Step 5: Continue stirring at high speed for 5 minutes, with the speed set to 50 rpm for rotation and 20 rpm for revolution.
[0048] Step 6: After the mixing is completed, pour the prepared flowable ultra-high performance concrete into the mold in 3 times. After each pouring, it needs to be fully vibrated, and the vibration time is about 60s.
[0049] Step 7: Let it sit for 1 day and remove the mold.
[0050] Step 8: Place the concrete test block in a standard curing box with a temperature of 21°C and a humidity of 98% for 4 days, and then transfer it to a high-temperature curing device with a temperature of 98°C and maintain it in a water bath for 3 days.
[0051] Step 9: Conduct indoor tests to determine the compressive strength and flexural strength of high performance concrete. The results are shown in Table 1.
[0052] Example 3: An ultra-high performance concrete mix based on a standard curing method, wherein the raw materials include PO 42.5 cement, natural sand, silica fume, fly ash, water, a water reducing agent, and fine hook steel fiber.
[0053] The method for preparing ultra-high performance concrete comprises:
[0054] Step 1: Use a set of sieves to screen the natural sand and divide it into three groups according to the particle size range: 0.15-0.3mm, 0.3-0.6mm, and 0.6-1.18mm. Mix them in a mass ratio of 1:3:3 to configure the selected graded natural sand.
[0055] Step 2: Pour 1 part of PO 42.5 cement, 0.25 parts of silica fume, 0.1 parts of fly ash and 1.59 parts of selected graded natural sand into a planetary mixer by mass, and dry-mix at high speed for 2 minutes until uniform. The speed is set to 50 rpm for rotation and 20 rpm for revolution.
[0056] Step 3: Mix 0.243 parts of water and 0.034 parts of high-performance water reducer by mass, add to the mixer, stir at high speed for 8 minutes, and set the speed to 50 rpm and 20 rpm.
[0057] Step 4: Evenly scatter 0.238 portions of fine hook steel fiber in the mixer, restart the machine and stir at high speed for 2 minutes to evenly distribute the steel fiber in the concrete. Set the speed to 50 rpm for rotation and 20 rpm for revolution.
[0058] Step 5: Continue stirring at high speed for 5 minutes, with the speed set to 50 rpm for rotation and 20 rpm for revolution.
[0059] Step 6: After the mixing is completed, pour the prepared flowable ultra-high performance concrete into the mold in 3 times. After each pouring, it needs to be fully vibrated, and the vibration time is about 60s.
[0060] Step 7: Let it sit for 1 day and remove the mold.
[0061] Step 8: Place the concrete specimens in a standard curing box at a temperature of 21°C and a humidity of 98% for 7 days.
[0062] Step 9: Conduct indoor tests to determine the compressive strength and flexural strength of high performance concrete. The results are shown in Table 1.
[0063] Table 1 Strength index of ultra-high performance concrete under different implementation plans
[0064]
[0065] In summary, it is obvious to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be regarded as exemplary and non-restrictive from any point of view, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention.
Claims
1. An ultra-high performance concrete based on a combined curing method, characterized in that: The invention comprises PO 42.5 cement, natural sand, silica fume, fly ash, water, water reducing agent and steel fiber, wherein the mass fractions of the PO 42.5 cement, natural sand, silica fume, fly ash, water, water reducing agent and steel fiber are 1, 1.59, 0.25, 0.1, 0.243, 0.034 and 0.238 respectively.
2. The ultra-high performance concrete based on the combined curing method according to claim 1, characterized in that: The particle gradation range of the PO 42.5 cement is relatively narrow, with 3-32 μm particles accounting for 60-70%; the SiO2 content of the silica fume is 85-90%; and the fly ash is Class II non-high-quality fly ash.
3. The ultra-high performance concrete based on the combined curing method according to claim 1, characterized in that: The natural sand is divided into three groups according to the particle size range: 0.15-0.3 mm, 0.3-0.6 mm and 0.6-1.18 mm, and is mixed in a mass ratio of 1:3:3 before use.
4. The ultra-high performance concrete based on the combined curing method according to claim 1, characterized in that: The natural sand, silica ash and fly ash are all taken from Ordos City. The silica ash and fly ash are solid wastes from local power plants and crystalline silicon plants in Ordos City. The prices of silica ash and fly ash after deep processing are about 30% lower. The application of silica ash and fly ash has greatly improved environmental benefits, reduced economic costs, and promoted the development of a low-carbon economy.
5. The ultra-high performance concrete based on the combined curing method according to claim 1, characterized in that: The water reducer is a polycarboxylic acid high-efficiency water reducer, which is prepared by dropwise addition of polyether water reducer monomer, hydrogen peroxide, VC, acrylic acid and mercaptopropyl functional monomer to generate an oxidation-reduction reaction.
6. The ultra-high performance concrete based on the combined curing method according to claim 1, characterized in that: The steel fiber is a thin hook steel fiber, the specification of the thin hook steel fiber is 0.22mm×13mm, and the hook steel fiber is taken from waste tires.
7. A method for preparing ultra-high performance concrete based on a combined curing method, used for the ultra-high performance concrete based on a combined curing method according to any one of claims 1 to 6, characterized in that: At least: Step 1: Pour cement, natural sand, silica fume and fly ash into a planetary mixer in proportion, and stir at high speed for 2 minutes until uniform. Set the speed to 50 rpm for rotation and 20 rpm for revolution. Step 2: Mix water and water reducing agent in proportion and add them into the mixer. Stir at high speed for 8 minutes. Set the speed to 50 rpm and 20 rpm. Step 3: Evenly scatter the steel fibers in the mixer, restart the machine and stir at high speed for 2 minutes to evenly distribute the steel fibers in the concrete. Set the speed to 50 rpm for rotation and 20 rpm for revolution. Step 4: Continue stirring at high speed for 5 minutes, with the speed set to 50 rpm for rotation and 20 rpm for revolution; Step 5: After the mixing is completed, pour the prepared flowable ultra-high performance concrete into the mold in three times. After each pouring, it needs to be fully vibrated for 60 seconds. Step 6: After standing for 1 day, remove the mold; Step 7: Place the concrete test block in a standard curing box at a temperature of 21°C and a humidity of 98% for 4 days, and then transfer it to a high-temperature curing device at a temperature of 98°C and maintain it in a water bath for 3 days; Step 8: Conduct indoor tests to determine the compressive and flexural strengths of ultra-high performance concrete.
8. The method for preparing ultra-high performance concrete based on a combined curing method according to claim 7, characterized in that: The compressive strength of the ultra-high performance concrete is 143 MPa, and the flexural strength of the ultra-high performance concrete reaches 24 MPa.
Citation Information
Patent Citations
Low cost active powder concrete and preparation thereof
CN101486554A
Active powder concrete and production technology for pouring fabricated component by active powder concrete
CN108821670A
Graphene oxide ultra-high performance concrete with low cement consumption and preparation method thereof
CN111377687A
AU2020101096A4